Using radial distribution functions to calculate cellular cross-absorbed dose for β emitters: comparison with reference methods and application for 18F-FDG cell labeling. (26th August 2021) - Jacquemin, M; Ribeiro, F; Aliane, K; Broggio, D; Franck, D; Desbrée, A
Abstract: To further improve the understanding of in vitro biological effects of incorporated radionuclides, it is essential to accurately determine cellular absorbed doses. In the case of β emitters, the cross-dose is a major contribution, and can involve up to millions of cells. Realistic and efficient computational models are needed for that purpose. Conventionally, distances between each cell are calculated and the related dose contributions are cumulated to get the total cross-dose (standard method). In this work, we developed a novel approach for the calculation of the cross-absorbed dose, based on the use of the radial distribution function ( rdf )) that describes the spatial properties of the cellular model considered. The dynamic molecular tool LAMMPS was used to create 3D cellular models and compute rdfs for various conditions of cell density, volume size, and configuration type (lattice and randomized geometry). The novel method is suitable for any radionuclide of nuclear medicine. Here, the model was applied for the labeling of cells with 18 F-FDG used for PET imaging, and first validated by comparison with other reference methods. Mean S cross values calculated with the novel approach versus the standard method agreed very well (relative differences less that 0.1%). Implementation of the rdf -based approach with LAMMPS allowed to achieved results considerably faster than with the standard method, the computing time decreasing from hours to seconds for 10 6 cells. The rdf -based approach was also faster and easier to accommodate more complex cellular models than the standard and other published methods. Finally, a comparative study of the mean S cross for different types of configuration was carried out, as a function of the cell density and the volume size, allowing to better understand the impact of the configuration on the cross-absorbed dose.